Exploring the Application of Restorative Environment Design in Coastal Area - Syahnas Nevysilia Kirana; Wendy Sunarya (Departement of Architecture, Universitas Islam Indonesia, 2024)
The coastal ecosystem provides biodiversity that is attractive for exploration and essential to support global life systems. However, these areas have become increasingly vulnerable due to climate change and human activities. Therefore, infrastructure development in coastal regions must prioritize sustainable practices to protect these ecosystems. This paper explores the potential of Restorative Environment Design (RED) in coastal zones, synthesizing fundamental principles from Attention Restoration Theory (ART), sustainable coastal infrastructure management, and multisensory human experiences in coastal environments. The study develops a design framework integrating three dimensions: (1) Identifying coastal management strategies, including habitat restoration, soft engineering, and eco-engineering; (2) Assessing multisensory properties and experiences of coastal zones; and (3) Applying the core components of restorative environments, including being away, fascination, extent, and compatibility. This study also presents a conceptual model for RED implementation in coastal zones based on the proposed design framework. The conceptual model illustrates how zoning strategies, guided by fundamental principles, can address ecological restoration while enhancing human well-being through restorative design. The results of this study ultimately provide insights for designing coastal spaces that promote mental recovery, community engagement, and long-term ecological sustainability. Keywords: Attention Restoration Theory (ART); Coastal Zoning Strategies; Ecological Restoration; Restorative Environment Design; Sustainable Coastal Development.